2022
DOI: 10.3389/fphar.2022.844756
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy and Skin Diseases

Abstract: Autophagy is a highly conserved lysosomal degradation system that involves the creation of autophagosomes, which eventually fuse with lysosomes and breakdown misfolded proteins and damaged organelles with their enzymes. Autophagy is widely known for its function in cellular homeostasis under physiological and pathological settings. Defects in autophagy have been implicated in the pathophysiology of a variety of human diseases. The new line of evidence suggests that autophagy is inextricably linked to skin diso… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 163 publications
0
25
0
Order By: Relevance
“…For example, Vasseur et al reported an increase in IL-17A-producing cells in the skin and an exacerbation of IMQ-induced psoriatic dermatitis in mice [ 100 ] when a high-fat diet containing saturated fatty acids was administered. In addition, prolonged exposure of primary epidermal keratinocytes to TNF-α decreases cathepsins levels in lysosomes with the consequent reduction in autophagy, a finding also observed in patients with psoriasis suggesting that psoriasis-associated cytokines, such as TNF-α and IL-17A, alter autophagy in keratinocytes [ 101 ].…”
Section: The Link Between Psoriasis and Obesitymentioning
confidence: 99%
“…For example, Vasseur et al reported an increase in IL-17A-producing cells in the skin and an exacerbation of IMQ-induced psoriatic dermatitis in mice [ 100 ] when a high-fat diet containing saturated fatty acids was administered. In addition, prolonged exposure of primary epidermal keratinocytes to TNF-α decreases cathepsins levels in lysosomes with the consequent reduction in autophagy, a finding also observed in patients with psoriasis suggesting that psoriasis-associated cytokines, such as TNF-α and IL-17A, alter autophagy in keratinocytes [ 101 ].…”
Section: The Link Between Psoriasis and Obesitymentioning
confidence: 99%
“…Upon induction of autophagy, LC3 is conjugated to phosphatidylethanolamine and targeted to autophagic membranes, thus an increased expression of LC3II represents and increased autophagy. Notwithstanding, it has to be taken into account that autophagy impairment in skin samples could not be an specific biomarker for AD, since autophagy is also impaired in skin diseases and other pathological conditions (Klapan et al, 2022); hence it has to be combined with other diagnostic criteria such as the detection of tau hyperphosphorylations and the clinical data.…”
Section: Discussionmentioning
confidence: 99%
“…The FAD is linked to mutations not only in PS1, but also in genes coding for AβPP and PS2, which lead to alterations in AβPP processing, generation of the Amyloid-β peptide and tau hyperphosphorylation. Accordingly, FAD animal models with mutations in PS1 show molecular, biochemical and physiological modifications including memory alterations (Sun et al, 2005;Mirnics et al, 2008;Elder et al, 2010;Lee et al, 2010), reduced survival (Wen et al, 2004;Veeraraghavalu et al, 2013), impaired synaptic function (Priller et al, 2007;Auffret et al, 2009;Ho and Shen, 2011), alterations in AβPP processing, increased Aβ levels (Yu et al, 2001;Arber et al, 2020) and increased tau phosphorylation (Pigino et al, 2001;Shepherd et al, 2004;Tanemura et al, 2006;Ochalek et al, 2017), that altogether lead to neurodegeneration (Chui et al, 1999;Nixon et al, 2005;Eskelinen, 2006;Maarouf et al, 2008;Armstrong et al, 2014;Struyfs et al, 2015;Cacace et al, 2016;Palmqvist et al, 2020;Klapan et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…This further gives rise to di culties in the treatment of AD. Therefore, in recent years, study about the correlation between psoriasis and AD has been going on [12] , but mostly restricted to clinical manifestations. The function and clinical relevance of their common molecular biomarkers in psoriasis and AD are less explored.…”
Section: Discussionmentioning
confidence: 99%
“…Autophagy was rstly put forward by Christian de Duve in 1963. Its main functions are to maintain the homeostasis of cells by self-eating senile tissues or some other unwanted metabolite [12] . In recent years, increasing studies reported the association of autophagy with immune system diseases, including atopic dermatitis (AD) and psoriasis [13] .…”
Section: Introductionmentioning
confidence: 99%